An aerial reconnaissance of livestock and human populations in relation to land use and ecological conditions in the SORDU project area of southern Ethiopia - Milligan, K. (International Livestock Centre for Africa, 1983)
Presents results of the first of a series of aerial reconnaissance surveys carried out by a joint ILCA/RDP team in the Southern Ethiopian rangelands, to count & map the distribution of livestock & Borana pastoralists as well as variations in rangeland & water conditions during the four main climatic periods characteristic of the area.